The Application of The Sustainable Development Concept In Indonesia’s Environmental Law - Nurmayani Nurmayani; Eka Deviani; Risa Mahdewi; Desia Rakhma Banjarani (Faculty of Law, Musamus University, 2021)
The reality of state life places the environment in sustainable development as an integral part of the national dynamics development. Moreover, Indonesia itself has issued various policies and instruments in the development of environmental law. Therefore, the development of environmental law cannot be separated from efforts to develop environmental law in accordance with international and national concepts or principles, one of which is the concept of sustainable development. However, environmental problems in Indonesia often occur, for example, forest fires, river pollution, air pollution, garbage, etc. This can raise doubts for the Indonesian people regarding the concept of sustainable development has really been applied in environmental law regulations in Indonesia so that it is necessary to examine the application of the sustainable development concept in Indonesia’s environmental law. Based on this background, the problem discussed in this paper is how the concept and application of sustainable development are in Indonesia’s environmental law? The method used in this article is normative legal research with a library law approach. The results of the study indicate that environmental law regulations in Indonesia such as: Law Number 4 of 1982 concerning Basic Provisions for Environmental Management, Law Number 23 of 1997 concerning Environmental Management, Law no. 32 of 2009 concerning Environmental Protection and Management, and Law no. 11 of 2020 concerning Job Creation, has been in accordance with the concept of sustainable development as stated in the articles in each of these laws.